Transition from bubble flow to slug flow along the streamwise direction in a gas–liquid swirling flow. (20th July 2019) - Liu, Wen; Bai, Bofeng
Highlights: Transition from bubble flow to slug flow under the effect of swirl was observed. Variation of interface morphology along the streamwise direction is analyzed. Mechanism for the transition to slug flow in the swirling flow is analyzed. A model is developed to predict the axial position for the transition to slug flow. Abstract: Transition from bubbly to slug flow is a well-known phenomenon. In the channel with a swirler, a transition to slug flow at a lower gas superficial velocity than in the same channel without the swirler was observed in this work. The transition phenomenon from bubble flow to slug flow under the effect of swirl in a circular pipe was observed and investigated. Compared to the flow pattern (maintaining the bubble flow along a streamwise direction) in a non-swirling flow, we observe that bubble flow is transformed to a gas column downstream of the swirler, then broken up, and finally separated into gas slugs in the streamwise direction. The dynamic condition for the occurrence of a liquid bridge is proposed, then combined with a swirl decay model of a gas–liquid two-phase swirling flow; thus, the axial position for the transition from a gas column to a slug flow along the streamwise direction can be predicted. Whether slug flow always remains along the streamwise direction is closely related to its size. Under the effect of swirl, the void fraction is decreased and the pressure drop is increased compared with that in a non-swirling flow, and gradually approximates the values of a non-swirling flow along the streamwise direction.